(untitled) (Progressive Agriculture, 2013)
This study elucidates an attempt to prepare compost from kitchen, dairy and drainage wastes and estimate their manorial value, and to examine the effect of prepared compost on the properties of post-harvest soil. The composts on individual item were prepared by the recently practiced quick composting method. The composts were applied in four different plots; three were treated with composts and the rest with no-treatment. The red amaranth was taken as the reference crop for the present study. The plots treated with dairy and kitchen wastes composts conserved the maximum soil moisture, available phosphorus and exchangeable potassium. The compost prepared from dairy wastes showed the best performance in conserving soil organic carbon and organic matter. The kitchen wastes compost supplied the maximum amount of nitrogen content to the soil. The dairy and kitchen wastes compost was better than the drainage wastes compost for sustainable crop production and in improving soil chemical properties and maintaining good soil quality. Dairy wastes compost showed the best performance in terms of canopy developing the plant height and root length. The highest yield was found in dairy and kitchen wastes compost treated plots. For growth and yield of red amaranth, dairy, kitchen and drainage wastes compost were superior to conventional farming as sustainable agricultural inputs. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16872 Progress. Agric. 20(1 & 2): 201 206, 2009